Hubungan Motivasi Perawat Dengan Pendokumentasian Asuhan Keperawatan Di Ruangan Rawat Inap Interne RSUD Kota Padang Panjang - Weni Lidya Hendayani (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Nursing documentation is evidence of the recording and reporting nurses in thecare records that are useful for the benefit of clients, nurses and health teams inproviding healthcare services on a basis of accurate and complete data in writing as nurses responsibilities (Wahid & Sunapto, 2012). The purpose of this researchis to know motivation relation with documentation of nursing care atinternal hospital room of RSUD Kota Padang Panjang Research method used inthis research is descriptive of korelasional by using cross-sectional design which isresearch plan with interview technique (Sugiyono, 2013) Based on the statisticaltest shows that there is a significant correlation between nurse motivation anddocumentation of nursing care in the internal hospital room of RSUD PadangPanjang with p value 0,002 < α (0,05) which means that Ho is rejected. Conclusion The presence of nurse antar motivation relationship with thedocumentation of nursing care in the inpatient room of RSUD Padang PanjangLong. Suggestion: It is expected that nurses who have good intrinsic motivationcan maintaining her motivation and for less motivated nurses, can further increaseber motivation Kata Kunci : Nursing Care Documentation; Nurse Motivation